INTERNATIONAL COOPERATION ON MARINE ENVIRONMENT PROTECTION OF OIL POLLUTION FROM VESSEL (A STUDY OF STRAITS MALACCA AND SINGAPORE) - Isfarin, Nadia Nuraini; Triatmodjo, Marsudi (Indonesian Journal of International Law, 2015)
This research is proposed to answer three problem. First, the rules of international law in the protection of the marine environment from oil pollution originating from vessel. Second, efforts were made by the three littoral countries cooperation in preventing, reducing and controlling oil pollution originating from vessel in the Straits of Malacca and Singapore. Third, the role of the government of Indonesia in prevention, reduce and control oil pollution originating from vessel in the Straits of Malacca and Singapore. This research is normative research using qualitative research methods. The research approach using statute approach and case approach. The results of this research shows that international law has been comprehensively regulate the protection of the marine environment from pollution by oil originating ships: the United Nations Convention on the Law of the Sea (UNCLOS) 1982, The International Convention for the Prevention of Pollution from Ship (MARPOL) 73/78, International Convention on Oil Pollution Preparedness 1980, the Civil Liability Convention for Oil Damage (CLC) 1992 and the Convention on the Establishment of an International Fund for Compensation for Oil Pollution Damage (FUND) 1992. Second, Indonesia, Malaysia and Singapore as states bordering the straits cooperate with other stakeholders (user states, user industries, IMO, NGOs) have established a cooperation mechanism in the form of cooperative forums, project coordination committee and the Aids to Navigation Fund. Third, Indonesia through its laws and regulations have ensured the prevention, reduction and control of oil pollution originating from vessel through Act No. 17 of 2008 on Shipping, Government Regulation No. 21 of 2010 on the Protection of Maritime Environment, and Presidential Decree No. 109 in 2006 on Disaster Emergency Due to Oil Spill in the ocean.